Describing characteristics of adults with and without congenital heart defects hospitalized with COVID‐19. Issue 12 (11th June 2022) - Diaz, Perla; Coughlin, Will; Lam, Wilson; Ermis, Peter; Aguilar, David; Ganduglia Cazaban, Cecilia M.; Agopian, A. J.
Abstract: Background: We sought to describe patient characteristics in adults with and without congenital heart defects (CHDs) during hospitalization for COVID‐19. Methods: We analyzed data collected by Optum®, a nationally representative database of electronic medical records, for 369 adults with CHDs and 41, 578 without CHDs hospitalized for COVID‐19 between January 1, 2020, and December 10, 2020. We used Poisson regression to describe and compare epidemiologic characteristics, heart‐related conditions, and severe outcomes between these two groups. Results: The distributions of many epidemiologic characteristics were similar between the two groups, but patients with CHDs were significantly more likely to be current or former smokers compared to patients without CHDs (risk ratio [RR]: 1.5, 95% confidence interval [CI]: 1.2, 1.8). Patients with CHDs were also significantly more likely to have heart failure, stroke, acute arrhythmia, myocardial injury, acute pulmonary hypertension, venous thromboembolism, and obesity documented at the time of the COVID‐19 hospitalization (RR range: 1.5–4.7) but not respiratory failure. Patients with CHDs (7 days) had a significantly longer median length of stay than those without CHDs (5 days; p < .001) and were significantly more likely to have an intensive care unit (ICU) admission (RR: 1.6, 95 CI: 1.2–1.9). Conclusions: Our description of patients among a large population improves our understanding of the clinical course of COVID‐19 among adults with CHDs. Adults with CHD appear to be at greater risk for more severe CHD, including greater risk of ICU admission and longer length of hospital stays.